2022
DOI: 10.1007/s00213-022-06244-z
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects of oral mitragynine and oxycodone in a rodent model

Abstract: Rationale Kratom derives from Mitragyna speciosa (Korth.), a tropical tree in the genus Mitragyna (Rubiaceae) that also includes the coffee tree. Kratom leaf powders, tea-like decoctions, and commercial extracts are taken orally, primarily for health and well-being by millions of people globally. Others take kratom to eliminate opioid use for analgesia and manage opioid withdrawal and use disorder. There is debate over the possible respiratory depressant overdose risk of the primary active alkalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…However it most robustly generalized to a nonscheduled alpha-adrenergic drug, lofexidine, which was approved by the FDA for treating opioid withdrawal, and the over-the-counter cold medicine, phenylephrine ( Reeve et al, 2020 ). These findings are consistent with the characterization of MG’s diverse pharmacology that includes effects at several opioid receptors in addition to agonism at adrenergic, serotonergic, D2-dopaminergic and adenosine receptors as discussed in Section 4.3 and other reviews and studies ( Kruegel et al, 2016 ; Kruegel et al, 2019 ; Henningfield et al, 2022c ; Qu et al, 2023 ; McCurdy et al, 2024 ).…”
Section: Kratom Use Disorder Withdrawal and Addictionsupporting
confidence: 88%
See 2 more Smart Citations
“…However it most robustly generalized to a nonscheduled alpha-adrenergic drug, lofexidine, which was approved by the FDA for treating opioid withdrawal, and the over-the-counter cold medicine, phenylephrine ( Reeve et al, 2020 ). These findings are consistent with the characterization of MG’s diverse pharmacology that includes effects at several opioid receptors in addition to agonism at adrenergic, serotonergic, D2-dopaminergic and adenosine receptors as discussed in Section 4.3 and other reviews and studies ( Kruegel et al, 2016 ; Kruegel et al, 2019 ; Henningfield et al, 2022c ; Qu et al, 2023 ; McCurdy et al, 2024 ).…”
Section: Kratom Use Disorder Withdrawal and Addictionsupporting
confidence: 88%
“…Although some organizations warned of opioid-type kratom overdose risks, the main mechanism of opioid overdose, respiratory depression, does not appear to be a substantial risk from kratom due to differences in the mechanisms of action and signaling pathways of MG and 7OHMG. Evidence suggests that this may reflect their relative weak recruitment of beta-arrestin at opioid receptors (e.g., Kruegel et al, 2016 ; Kruegel et al, 2019 ; Henningfield et al, 2022c ; Qu et al, 2023 ; McCurdy et al, 2024 ). As discussed, MG’s relatively weak respiratory effects as compared to morphine-like opioids may also reflect the “balanced agonist effects of diverse kratom alkaloids and metabolites” ( Hill et al, 2022 ; Qu et al, 2023 ).…”
Section: Epidemiology: Safety Risks Associated Deaths and Public Heal...mentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced respiratory depression of mitragynine compared to codeine was reported more than 50 years ago [14]. Furthermore, mitragynine and 7-hydroxymitragynine are also bound to adrenergic (α 1 and α 2 ) and serotonergic (5-HT 1A and 5-HT 2B ) receptors, producing a different profile of effects than prototypical opioids [16,[21][22][23]. Currently, based on this unique pharmacology, there is substantial interest in the development of synthetic medicinal compounds built on the chemical scaffolding of kratom alkaloids for analgesia, namely, for the treatment of opioid withdrawal and opioid use disorder [17,19,24].…”
Section: Introductionmentioning
confidence: 99%
“…MG possesses a poly-pharmacological profile and a primary opiate receptor activity, with preliminary evidence suggesting the possibility of mu-opioid receptor (MOR) activity without β-arrestin-2 recruitment in the signaling pathway [ 10 •]. Recent evidence has shown that high doses (between 20 and 400 mg/kg) of oral MG do not exert respiratory depression compared to oxycodone in animal models [ 11 ]. However, information related to the safety profile of MG is still quite limited.…”
Section: Introductionmentioning
confidence: 99%